BE A TEACHER IN CHILD EDUCATION: GENDER AND TEACHING - Ruis Sciotti, Fernando Ferrari [UNESP]; Argenti Perez, Marcia Cristina [UNESP]; Bellido, Luciana Ponce [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
The present work has as objective to present the life and professional trajectory of a teacher of the Infantile Education, as well as some questions of gender involving the teaching. The research took place in a municipal pre-school. For the data collection qualitative research strategies were used such as participant observation and semi-structured interview. We apprehend moments of interaction of the teacher with his class of students and their daily practices. Through his stories, the teacher revealed how he was entering the profession, the challenges and the obstacles faced. We conclude that the entry of male teachers at this stage of education can contribute to deconstruct naturalized conceptions about the profession, as well as breaking with the image of the woman as educator of small children.
Keywords: Gender; Teaching; Early childhood education